PROFIL KECEMASAN ORANG TUA PADA PERILAKU REMAJA DI JORONG AUR KUNING KECAMATAN MAPAT TUNGGUL SELATAN KABUPATEN PASAMAN - IYAS, IYAS; Ibrahim, Indra; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Adolescentâs are the future generation that have many changes in good behavior to be better. Even thought be worse to achieve the good behavior needed the role of parent in fact some parent have with the change of the teenâs behavior . the problem of this research how the profile of parentâs anxienty with the teenagerâs behavior. The important of this research to describe about the parentâs anxiety with teenagerâs behavior. This research is descriptive research that describe about the original condition. The population in this research are the perents in Jorong Aur Kuning Kecamatan Mapat Tunggul Selatan Kabupaten Pasaman amounted 41. Perents this research use the 41 samples, to take the sample with use total sampling. The resourees of data in this research are primary data and secondary data. The result of data will be organized with use presentation technigue. The finding of this research explain the parentâs anxiaty with the teengers behavior in Jorong Aur Kuning Kecamatan Mapat Tunggul Selatan Kabupaten Pasaman seen from the psychological aspect and physicologal aspect in the hight care gory it meanâs that, the parentâs anxiety towar the teengerâs behavior is better. So, suggested to the parentâs to control the anxiety to face the teenagerâs behavior